Routine Bone Imaging for Metastatic Renal Cell Carcinoma: Is it Time? (Journal of Kidney Cancer, 2021)
Current guidelines by the National Comprehensive Cancer Network recommend that, in addition to routine computed tomography (CT) imaging, bone imaging and brain magnetic resonance imaging (MRI) should be obtained when clinically indicated. In this issue of the Journal of Kidney Cancer and VHL, a systematic literature review of clinical trials of metastatic renal cell carcinoma (mRCC) patients evaluates the incidence of osseous, lymph node, and lung metastases (1). In particular, the analysis by Lin et al focuses on the changes in incidence over time. The study finds that the incidence of bone, lymph node, and lung metastases has increased over time. This increase is significant in osseous metastases specifically. These results lead to two provocative questions. First, why have osseous metastases increased in incidence over time? Second, does this finding warrant a more aggressive and uniform approach to imaging to identify osseous metastases sooner?